Sighting of Rose-ringed Parakeet (blue) at Kachoriya nala from Rawatbhata, Chittorgarh district, Rajasthan, India - Jain, Charchit; Gupta, Akshun; Sudhindran, Rimal (Journal of the Bombay Natural History Society (JBNHS), 2014)
No Abstract.